2015
DOI: 10.1093/cercor/bhv205
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Development of Cortical and White Matter Structure in the NCANDA Sample: Role of Sex, Ethnicity, Puberty, and Alcohol Drinking

Abstract: Brain structural development continues throughout adolescence, when experimentation with alcohol is often initiated. To parse contributions from biological and environmental factors on neurodevelopment, this study used baseline National Consortium on Alcohol and NeuroDevelopment in Adolescence (NCANDA) magnetic resonance imaging (MRI) data, acquired in 674 adolescents meeting no/low alcohol or drug use criteria and 134 adolescents exceeding criteria. Spatial integrity of images across the 5 recruitment sites w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
147
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 130 publications
(165 citation statements)
references
References 111 publications
13
147
0
5
Order By: Relevance
“…6 Similarly, in 2012-2013, consumption magnifies the risk. 1,3,9,10 The initiation of alcohol use occurs alongside changes in life roles and neurobiological maturation 11 and, therefore, has the poten tial to disrupt processes critical to the suc cessful transition from childhood to adulthood. Educational achievement is an important determinant of how well this developmental stage is navigated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Similarly, in 2012-2013, consumption magnifies the risk. 1,3,9,10 The initiation of alcohol use occurs alongside changes in life roles and neurobiological maturation 11 and, therefore, has the poten tial to disrupt processes critical to the suc cessful transition from childhood to adulthood. Educational achievement is an important determinant of how well this developmental stage is navigated.…”
Section: Introductionmentioning
confidence: 99%
“…impaired memory and decision making), among heavy drinking adolescents compared to their non/low drinking peers. 10,23,24 Frequent binge behav iour appears especially harmful, based on associations between the quantity and fre quency of alcohol consumption with the persistence and degree of structural and functional abnormalities. 3,911 As the major ity of studies have been crosssectional in design, questions persist regarding whether reported neurocognitive differences predate (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This report provides an overview of NCANDA's methodology and characterizes the sample at baseline. Other reports provide analysis of this sample on cognitive and motor performance, comprehensive clinical measures, sleep hygiene, regional brain macrostructure based on magnetic resonance imaging (MRI)-derived metrics (Pfefferbaum et al, 2015), regional brain white matter microstructural metrics derived from MR diffusion tensor imaging (DTI), and resting state MRI (rsMRI).…”
mentioning
confidence: 99%
“…Si la consommation d'alcool avant l'âge légal est souvent considérée comme un comportement transitoire courant reflé-tant une tendance accrue à prendre des risques pendant cette phase, les experts affirment que les adolescents sont particulièrement susceptibles de subir les effets négatifs de cette consommation, et les abus occasionnels en amplifient les risques 1,3,9,10 . En effet, la consommation d'alcool intervient pendant une période de maturation neurobiologique caractérisée par la modification des rôles dans la vie 11 et, de ce fait, elle peut perturber certains processus essentiels à une transition réussie entre l'enfance et l'âge adulte.…”
Section: Introductionunclassified